An Analysis of Impoliteness Strategies in Indonesia Issue on X - Rahma, Alya Vania; Hutagalung, Afifah Syahlina Br; Nasution, Diantry Binarwati Habibie; Lhaksmi, Maha; Rangkuti, Rahmadsyah (Journal of English Language and Education, 2025)
This study investigates Indonesian political discourse on X (formerly Twitter), focusing on public reactions to the government's Nutritious Food Program (MBG). It explores how netizens deploy rudeness strategies to articulate political views, grievances, and ideological stances. Data were collected via purposive sampling of ten public comments from the @salam4jari account on MBG-related posts. Employing a qualitative descriptive approach, the analysis applies Culpeper's impoliteness framework, encompassing updated categories (affective, coercive, entertaining) and classical ones (bald on record, positive, negative, sarcasm/mock politeness, withhold politeness). Findings reveal users frequently venting anger, dissatisfaction, or humor through direct verbal aggression, sarcasm, and emotional outbursts. Affective impoliteness appears in emotionally charged attacks, coercive in forceful demands for policy shifts, and entertaining in amusing yet degrading insults. The lack of withhold politeness suggests open rather than covert dissent. Overall, impoliteness serves as emotional catharsis and a tactic for bolstering group identity, wielding power, and challenging dominant narratives. This research enriches insights into digital communication in polarized contexts, underscoring the sociocultural dynamics of online linguistic behavior.